Mobile learning for instructional purpose in Nigeria : an exploratory analysis - Ifinedo, Eloho (2013)
The main purpose of this research is to explore the use of M - learning for instructional purpose in Nigeria with a view to uncovering the degree to which it is in use in the institutions of learning. The issue was addressed from the view point of students and also from the theoretical point drawn from relevant extant literatures of other students and some learning theories, frameworks as well as relevant literatures were examined. This research is empirical in nature and as such employs a cross sectional approach which involved the use of survey design in collecting data from students of different departments from two highly rated and recognized universities in Nigeria. Finally, the result of the study is presented and findings were discussed. The study offers findings to the research questions which comprised of the students commuting habits, ownership of the mobile device, skill, access to the internet as well as their disposition towards adopting mobile learning. This is because these factors among others, were identified as critical to the implementation of m – learning. Ultimately, the findings of this work should help and guide future research works and policy makers. It is also valuable for identifying ways to contribute to improving the learning experience in Nigeria and by extension Africa using the mobile technology.